2014
DOI: 10.3389/fnagi.2014.00162
|View full text |Cite
|
Sign up to set email alerts
|

Cotinine halts the advance of Alzheimer's disease-like pathology and associated depressive-like behavior in Tg6799 mice

Abstract: Alzheimer's disease (AD) is associated with cognitive and non-cognitive symptoms for which there are currently no effective therapies. We have previously reported that cotinine, a natural product obtained from tobacco leaves, prevented memory loss and diminished amyloid-β (Aβ) plaque pathology in transgenic 6799 mice (Tg6799 mice) when treated prior to the development of the pathology. We have also shown that cotinine reduces depressive-like behavior in normal and chronically stressed C57BL/6 mice. Here, we ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
32
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 82 publications
3
32
0
Order By: Relevance
“…Several previous studies reported enhanced learning and memory after chronic cotinine administration in rodents (Terry et al ., , ; Buccafusco & Terry, ; Echeverria et al ., ; Moran, ; Gao et al ., ; Grizzell & Echeverria, ; Grizzell et al ., ; Patel et al ., ; Levin et al ., ). Chronic subcutaneous cotinine treatment did not significantly affect memory in wild‐type rats (Terry et al ., ), but chronic oral cotinine treatment enhanced spatial working memory in wild‐type mice compared to vehicle‐treated mice (Grizzell et al ., ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several previous studies reported enhanced learning and memory after chronic cotinine administration in rodents (Terry et al ., , ; Buccafusco & Terry, ; Echeverria et al ., ; Moran, ; Gao et al ., ; Grizzell & Echeverria, ; Grizzell et al ., ; Patel et al ., ; Levin et al ., ). Chronic subcutaneous cotinine treatment did not significantly affect memory in wild‐type rats (Terry et al ., ), but chronic oral cotinine treatment enhanced spatial working memory in wild‐type mice compared to vehicle‐treated mice (Grizzell et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…Activation of nAChRs promotes the expression of synaptic proteins in the brain and enhances cognition in animal models (Buccafusco & Terry, ; Terry et al ., , ; McKay et al ., ; Grizzell et al ., ). For example, cotinine treatment restored impaired memory in mouse and monkey models of impaired hippocampal function (Echeverria et al ., ; Terry et al ., ; Gao et al ., ; Grizzell et al ., ; Patel et al ., ), ameliorated impaired cognition in mouse models of Alzheimer's disease, including working memory (Echeverria et al ., ; Patel et al ., ), memory deficits in animal models of schizophrenia (Buccafusco & Terry, ; Buccafusco et al ., ; Terry et al ., ) and stress‐related memory impairments (Zeitlin et al ., ; Grizzell et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…For example, relevant to AD, cotinine has been shown to be cytoprotective and neuroprotective as demonstrated by its ability to improve the survival of differentiated PC12 cells deprived of nerve growth factor [40], as well as to protect primary cortical neurons from the neurotoxic effects of the amyloid beta (Aβ) peptide or glutamate [41,42]. Cotinine also improved working/short term memory in a delayed match to sample (DMTS) task in monkeys [43], prevented memory loss in an AD mouse model (Tg6799), stimulated the Akt/GSK3β pathway and reduced Aβ aggregation in their brains [44,45]. In studies more relevant to schizophrenia, cotinine attenuated the deficits in prepulse inhibition (PPI) of the acoustic startle response induced in three pharmacologic impairment models in rats [43], it improved sustained attention in rats that were impaired by the NMDA receptor antagonist MK-801 [46], and it attenuated deficits in working/short term memory in monkeys produced by the NMDA antagonist ketamine [47].…”
Section: Cotinine As a Prototypic Compound With “Multifunctional” mentioning
confidence: 99%
“…For example, in studies relevant to AD, cotinine has been shown to improve the survival of differentiated PC12 cells deprived of nerve growth factor (Buccafusco and Terry, 2003), as well as primary cortical neurons exposed to toxic concentrations of the amyloid-b peptide or glutamate Gao et al, 2014). Cotinine has also been shown to improve working/short-term memory performance in monkeys (Terry et al, 2005), prevent memory loss in transgenic 6799 Alzheimer's disease mice, and stimulate the Akt/GSK3b pathway and reduce amyloid-b aggregation in mouse brains Patel et al, 2014). In animal studies more closely related to schizophrenia, cotinine improved deficits in prepulse inhibition of the acoustic startle response in rats in three pharmacologic impairment models (Terry et al, 2005), attenuated the deficits of sustained attention in rats induced by the N-methyl-D-aspartate receptor antagonist MK-801 [(5S,10R)-(1)-5-methyl-10,11-dihydro-5H-dibenzo [a,d] cyclohepten-5,10-imine] (Terry et al, 2012), and improved deficits in working/short-term memory produced by the N-methyl-D-aspartate antagonist ketamine in monkeys (Buccafusco and Terry, 2009).…”
Section: Introductionmentioning
confidence: 99%